Design and Evaluation of Walking, Sit-To-Stand, and Stand-To-Sit Control Strategies for a Hip-Knee-Ankle-Foot Prosthesis with Motorized Hip Joint - Golshan, Farshad (Université d'Ottawa | University of Ottawa, 2025)
Hip disarticulation (HD) amputation involves the removal of the entire lower limb and the hip joint, adversely affecting mobility and quality of life. Depending on their physical condition and life goals, some people with amputation are prescribed a hip-knee-ankle-foot (HKAF) prostheses to regain mobility. However, HKAF prostheses are known to have a high rejection rate compared to transfemoral and transtibial prostheses, primarily due to their excessive energy demands and the physical fitness required for effective use. Despite advancements in motorized prosthetic joints for the knee and ankle, innovation for HKAF prostheses has stagnated. This thesis addresses this gap by developing and evaluating adaptive control strategies for a motorized HKAF prosthesis to enhance mobility for HD amputees. Based on preliminary mechanical development of the first viable motorized hip joint (Power Hip), this thesis developed and refined the electronics, sensors, and control system to enable people with hip level amputations to walk, sit, and stand. A prototype Powered Hip prosthesis was tested against a conventional passive prosthesis (Otto Bock Helix hip, C-Leg knee, Terion K2 foot) in a single HD participant. The Theia Markerless motion analysis system and Visual3D were used for kinematic and kinetic analyses. During walking, the Power Hip reduced pelvic tilt range from 22.77° ± 5.76° to 6.72° ± 1.49°, minimizing compensatory pelvic movements. Hip extension range improved from -0.22° ± 0.77° to -7.04° ± 2.85°, enabling a more natural stride by stabilizing the hip throughout the gait cycle. During sit-to-stand, ground reaction forces (GRF) on the prosthetic side increased from 0.30 ± 0.67 N/kg to 2.69 ± 0.34 N/kg, while stand-to-sit GRF rose from 4.28 ± 1.00 N/kg to 5.37 ± 0.52 N/kg. These enhancements improved load distribution, reducing intact-limb forces and aligning kinetic profiles more closely with transfemoral amputee patterns. By achieving movement biomechanics comparable to transfemoral prosthesis users, this research reimagined what HKAF prostheses can achieve. This research lays the foundation for a new generation of user-friendly prosthesis that prioritize mobility, independence, and quality of life for people with hip-level amputations.
Keywords: Power Hip; Prosthetics; Control system; Biomechanics; Hip disarticulation